Isolation And Amplification Of Fem – A Gene From Mrsa Isolates - S. GANESH MANIKANDAN; M. HEMALATHA; C. LAKSHMINARASIMHAN; N. THAJUDDIN (International Journal of Pharma and Bio Sciences, 2011)
Statphylococcus aureus is a Gram positive bacterium, which is naturally present in nasopharyngeal region of human beings and animals. After 1941, S.aureus was developed drug resistant capacity to against all penicillin antibiotics. In 1961, Methicillin Resistant Staphylococcus aureus were isolated. The present study Methicillin Resistant S. aureus were isolated from clinical pus samples. All isolates were grown on Luria Bertani (LB) Agar containing Oxacillin antibiotic. Genomic DNA isolated from isolates using with standard procedure. Fem A gene amplification using with Real Time PCR and suitable primers. The amplified gene was produced 510 bp at Agarose Gel Electrophoresis.